Eat All You Can in an All-You-Can-Eat Buffet: A Case for Aggressive Resource Usage - Mahajan, Ratul; Padhye, Jitu; Raghavendra, Ramya; Zill, Brian and (HotNets-VII, 2008)
In contrast to a focus on efﬁciency, we advocate aggressive usage of available resources. This view is embodied in what we call the Buffet principle: continue using more resources as long as the marginal cost can be driven lower than the marginal beneﬁt. We illustrate through several examples how this seemingly obvious principle is not adhered to by many common designs and how its application produces better designs. We also discuss broadly the considerations in applying the Buffet principle in practice.